2016
DOI: 10.1155/2016/3756302
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction and Aortic Root Mycotic Aneurysm Complicating Aortic Valve Endocarditis: Utility of Cardiac CT

Abstract: Aortic mycotic aneurysms are a rare but life-threatening potential complication of infective endocarditis. Rapid deterioration of the vascular wall in highly focal areas makes these pseudoaneurysms particularly prone to rupture, resulting in uncontrolled aortic hemorrhage. While computed tomography angiography (CTA) is the imaging modality of choice for the evaluation of mycotic aneurysms, it is not routinely performed in patients with known or suspected infective endocarditis (IE). However, current valvular h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Osteopontin (Opn) is a secreted glycosylated phosphoprotein, having important function in the extracellular matrix. Previous studies suggested that Opn can upregulate the expression of matrix metalloproteinases (MMPs) and thus accelerate the degradation of extracellular matrix, promoting aneurysm rupture and tumor metastasis (4,5). …”
Section: Introductionmentioning
confidence: 99%
“…Osteopontin (Opn) is a secreted glycosylated phosphoprotein, having important function in the extracellular matrix. Previous studies suggested that Opn can upregulate the expression of matrix metalloproteinases (MMPs) and thus accelerate the degradation of extracellular matrix, promoting aneurysm rupture and tumor metastasis (4,5). …”
Section: Introductionmentioning
confidence: 99%